Metallurgical investigations on 17th century Maratha Shivrai copper coins - Meenakshi Singh; Singh Manager Rajdeo (Zaštita Materijala)
The technical and numismatic complexities of Maratha Shivrai copper coins have been well documented. However, more information still needs to be on the chemical, mineralogical, microstructure composition, and metallurgical process employed for coin minting. Five Shivari coins (17-18 century CE) were studied under ED-XRF, XRD, and cross-sectional analysis by SEM-EDX. Scientific investigations reveal that the Maratha practiced excellent cupellation techniques to remove most ore impurities. The ED-XRF data on the surface and interior indicate that the coin comprises pure copper, and copper content varies between 97.73% to 100%. The coin surfaces are free from ore impurities like sulphur, Lead, tin, phosphorus, etc., and the black stains observed are due to copper mineralization detected through XRD analysis. There is a slight iron concentration gradient on the coin surfaces (4.48%) vis-à-vis the inner core (0.14%). Cros-ssectional analysis revealed many cracks and cavities in the coin interior due to copper mineralization threatening its stability if not taken care of. The archaeo-metallurgical studies of the coin interior reveal that significant impurities like Lead, sulphur, tin, iron, etc., are present in traces due to excellent polling, and Shivrai is a single-phase copper coin.